2021
DOI: 10.3390/polym13183114
|View full text |Cite
|
Sign up to set email alerts
|

One Surface Treatment, Multiple Possibilities: Broadening the Use-Potential of Para-Aramid Fibers with Mechanical Adhesion

Abstract: Aramid fibers are high-strength and high-modulus technical fibers used in protective clothing, such as bulletproof vests and helmets, as well as in industrial applications, such as tires and brake pads. However, their full potential is not currently utilized due to adhesion problems to matrix materials. In this paper, we study how the introduction of mechanical adhesion between aramid fibers and matrix material the affects adhesion properties of the fiber in both thermoplastic and thermoset matrix. A microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…The exact value appeared slightly lower than that of the un-sized rCF s but was well within the deviation range, as seen from Figure 3 b. The increased surface topography of rCF S was most likely the main contributor to the enhanced IFSS, as noted in other similar studies [ 19 , 27 , 28 , 29 ]. The surface of both of the rCF types (conventional and reactive pyrolysis) was more textured and rougher in the loading direction than of the pristine CFs ( Figure 1 ).…”
Section: Resultssupporting
confidence: 81%
“…The exact value appeared slightly lower than that of the un-sized rCF s but was well within the deviation range, as seen from Figure 3 b. The increased surface topography of rCF S was most likely the main contributor to the enhanced IFSS, as noted in other similar studies [ 19 , 27 , 28 , 29 ]. The surface of both of the rCF types (conventional and reactive pyrolysis) was more textured and rougher in the loading direction than of the pristine CFs ( Figure 1 ).…”
Section: Resultssupporting
confidence: 81%
“…A tough interface can enhance the fatigue tolerance of composites [14,15]. Common methods to enhance interfacial toughness are chemical grafting of polymer chains on reinforcing fibres to induce polymer chain entanglement between fibre and matrix [16,17], depositing functionalised nanomaterials on the fibres [18][19][20], and deploying a thin ductile phase between fibre and matrix [10,13]. For instance, Hsieh et al [15] showed that adding 0.5 wt% carbon nanotubes increases epoxy resin's fatigue crack growth threshold by 204% from 24 J/m 2 to 73 J/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Although the IFSS was lower than that of the reference, it was still in the same range as epoxy−aramid (29.8−54.2 MPa) but lower than epoxy-glass fiber (52.7 MPa), measured with the same device. 27,41 ■ CONCLUSIONS This work demonstrates the successful continuous conversion of dry-jet wet spun lignin−cellulose PFs (50/50 wt/wt) into CFs using softwood kraft lignin and cellulose pulp as sources.…”
Section: ■ Introductionmentioning
confidence: 78%
“…4 Although the IFSS was lower than that of the reference, it was still in the same range as epoxy–aramid (29.8–54.2 MPa) but lower than epoxy-glass fiber (52.7 MPa), measured with the same device. 27 , 41 …”
Section: Resultsmentioning
confidence: 99%